IS1245 restriction fragment length polymorphism typing of Mycobacterium avium from patients admitted to a reference hospital in Campinas, Brazil - Panunto,A.C. (2003)
Mycobacterium avium is an important pathogen among immunodeficient patients, especially patients with AIDS. The natural history of this disease is unclear. Several environmental sources have been implicated as the origin of this infection. Polyclonal infection with this species is observed, challenging the understanding of its pathogenesis and treatment. In the present study 45 M. avium strains were recovered from 39 patients admitted to a reference hospital between 1996 and 1998. Species identification was performed using a species-specific nucleic acid hybridization test (AccuProbe®) from Gen-Probe®. Strains were genotyped using IS1245 restriction fragment length polymorphism typing. Blood was the main source of the organism. In one patient with disseminated disease, M. avium could be recovered more than once from potentially sterile sites. Strains isolated from this patient had different genotypes, indicating that the infection was polyclonal. Four patient clones were characterized in this population, the largest clone being detected in eight patients. This finding points to a common-source transmission of the organism.